Investigation of accuracy of PPP and PPP-AR methods for direct georeferencing in UAV photogrammetry - Ocalan, Taylan; Turk, Tarik; Tunalioglu, Nursu; Gurturk, Mert (SPRINGER HEIDELBERG, 2022)
Traditionally, photogrammetric product accuracy at cm level is obtained with Ground Control Points (GCP) in UAV photogrammetry. In recent years, UAVs equipped with Post-Processing Kinematic & Real-Time Kinematic (PPK/RTK) have become widespread. Accuracy in cm-level can be obtained with relative/differential positioning with these equipment. On the other hand, PPP (Precise Point Positioning), which is a special type of absolute positioning, is used effectively in many applications. In this study, performances of PPP and PPP-AR (PPP positioning with ambiguity resolution) solutions of kinematic GNSS data obtained from UAVs were investigated and compared with PPK solutions based on relative positioning. Especially, the performance and potential of the PPP-AR approach in terms of quality and accuracy of the products generated in UAV-photogrammetry has been demonstrated. Thus, this study can significantly contribute to subjects such as the production of fast, accurate, and cost-effective products with UAV photogrammetry, earth sciences applications, precise agriculture, sustainable forest management, forest planning.
Keywords: UAV; Direct georeferencing; Photogrammetry; PPP; PPP-AR; GPS; FREQUENCY; Computer Science; Geology